Object identity representation occurs early in the archerfish visual system - Svetlana Volotsky; Ronen Segev (Scientific Reports)
Abstract Archerfish hunt by shooting a jet of water at aerial targets, a behavior used to study their visual processing by presenting a set of images on a screen above the water tank and observing the behavioral response. Building on this unique behavior, it was recently shown that archerfish can be trained to distinguish between different object categories by generalizing from examples. Analysis of the archerfish’s behavior revealed that the fish visual system relies on a small set of visual features for categorization and is more sensitive to object contours than to textures. To understand the neural basis of this object recognition, we investigated the neural representation of features and objects in the archerfish optic tectum using recording of single cells. We found that, although the optic tectum is an early stage of visual processing, a small population of neurons in this region contains information about the object category. This contrasts with the primate visual system, where the representation of objects emerges only at later stages of visual processing. These results suggest that early-stage feature extraction and object categorization in archerfish might represent a form of specialized visual processing. This contributes to a broader understanding of visual processing across taxa.